Agarose Micro‐Well Platform for Rapid Generation of Homogenous 3D Tumor Spheroids. Issue 7 (20th July 2021) - Krishnan, Mena Asha; Yadav, Kratika; Chelvam, Venkatesh
Abstract: In recent years, 3D culture of tumor spheroids has managed to revolutionize cancer research and drug discovery. 2D monolayer cells grown in cell culture flasks undergo radical changes in cell behavior, structure, and function owing to varying environmental cues and are unable to provide predictive data for preclinical evaluation. 3D tumor spheroids can better recapitulate tumor architecture, cell‒cell and cell‒matrix connectivity, and the tissue complexity of tumors grown in animal models. However, many of the existing techniques to culture 3D spheroids are time‐consuming and ineffective and produce irregular‐shaped spheroids that cannot be easily incorporated in biological assays. The set of protocols described herein makes use of a commercial hair brush as a template to create concave micro‐well impressions in agarose. This technique is easy, inexpensive, and adaptable and also has the ability to produce uniform, homogenous cancer spheroids, with large diameter (∼1000 μm) and thickness (∼250 μm), within 24 to 48 hr after cell seeding. The 3D spheroids produced using the agarose micro‐well platform function as an excellent 3D in vitro model for understanding the extent of penetration, uptake, and distribution of targeted cargos such as a diagnostic or therapeutic agents for identification and treatment of cancer. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Fabrication of agarose micro‐well scaffold for growing tumor spheroids using a commercial hair brush Basic Protocol 2 : Formation of homogenous tumor spheroids in agarose micro‐well platform Basic Protocol 3 : Assessing viability of 3D tumor spheroids grown in agarose micro‐wells using confocal microscopy Basic Protocol 4 : Analyzing uptake and penetration of targeted fluorescent bioconjugate in 3D tumor spheroids using two‐photon imaging